Genetic association between body composition measured by ultrasound and visual scores in Brazilian Nelore cattle - Gordo, D. G. M. [UNESP]; Baldi, Fernando [UNESP]; Lobo, R. B.; Koury Filho, W.; Sainz, R. D.; Albuquerque, Lucia Galvão de [UNESP] (Amer Soc Animal Science, 2012)
The objective of this study was to evaluate the genetic variability of body composition traits measured by ultrasound, growth traits, and visual scores as well as their genetic associations in Nelore cattle. A total of 9,765, 13,285, 13,061, 12,811, 3,484, 3,484, 3,483, and 3,303 records of weight at time of ultrasound measure (W550), 12th-13th rib LM area (LMA), backfat thickness (BF), rump fat thickness (RF), visual scores for body structure (BS), finishing precocity (FP), muscling (MS), and sheath and navel characteristics (SN), respectively, were used. The model included contemporary group (defined as year and season of birth, sex, and management group) as a fixed effect and age of dam at calving and age of the animal (linear and quadratic effects) as covariates. The direct additive genetic effect was included as a random effect. The analyses also included 46,157 observations of BW adjusted to 120 d. The (co)variance components were estimated by the restricted maximum likelihood method using a multitrait animal model. Heritability estimates for W550, LMA, BF, RF, BS, FP, MS, and SN were 0.37 +/- 0.030, 0.33 +/- 0.03, 0.24 +/- 0.02, 0.28 +/- 0.03, 0.24 +/- 0.04, 0.38 +/- 0.05, 0.29 +/- 0.05, and 0.38 +/- 0.06, respectively. The estimated genetic correlations between visual scores and LMA were moderate and positive, ranging from 0.37 to 0.44. Similar results were obtained for the estimated genetic correlations between FP and MS with fat thickness measures (BF and RF). Low genetic correlations were estimated between SN and BS and between SN and the body composition traits, indicating that selection for body composition traits and BS will not affect sheath and navel size. The estimated genetic correlations between weight adjusted to 120 d of age (W120) and W550 and BS were high (0.87 and 0.91) and moderate with LMA (0.49 and 0.55), FP (0.37 and 0.41), and MS (0.47 and 0.55). The visual scores and ultrasound-measured body composition traits have enough genetic variation for selection purposes in Nelore cattle. Selection based on visual scores for body structure, finishing precocity and muscling should lead to desired changes in body composition albeit much more slowly than direct selection on those traits measured by ultrasound. Selection for heavier BW at early ages should lead to favorable changes in yearling LM area and visual scores.
Keywords: Beef cattle; Fat thickness; Genetic correlation; Heritability; Longissimus muscle area; visual evaluation